TEHNIK ISYABA SOLUSI UNTUK MENGEMBANGKAN KEMAMPUAN KOMUNIKASI UNTUK ANAK TUNAGANDA ( TUNARUNGU DAN TUNANETRA) - Sulati Sulati (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2020)
Students with special needs are deaf and visually impaired, which are different from how to handle them as well as their characteristics, children with special needs who are deaf can understand language by optimizing their vision or are also called blind children because they rely on their visual abilities, while students with special needs blind people rely on their verbal language and touch in interacting and communicating with their environment both at school and at home. Isyaba technique is also called isyabat raba technique, this technique is given by combining the two existing abilities of students with multiple special needs. Namely visual abilities that cannot develop in students with multiple special needs combined with the touch of the fingers in recognizing letters, words, until they are able to compose words into a simple sentence. The use of isyaba techniques carried out in school cannot be done by the teacher alone, teachers can work closely with therapists, such as speech and language therapists, speech and language therapists, physical and occupational therapy and collaborate with other classroom teachers, as well as with parents. Isyaba technique is important to give to children with disabilities because the isyaba technique aims at developing social and academic skills, in addition to encouraging better attitude changes.